2011
DOI: 10.1039/c1sc00366f
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective intramolecular allylic C–H amination versus CC aziridination through Co(ii)-based metalloradical catalysis

Abstract: Excellent chemoselectivity for intramolecular allylic C-H amination versus C]C aziridination was achieved through Co(II)-based metalloradical catalysis. Metalloradical catalyst [Co(P1)], the cobalt(II) complex of D 2h -symmetric porphyrin 3,5-Di t Bu-IbuPhyrin, was shown to be highly effective for selective intramolecular allylic C-H amination of both N-bishomoallylic and N-allylic sulfamoyl azides. The Co(II)-catalyzed intramolecular 1,6-C-H amination of these azides provides a general and efficient method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 91 publications
5
60
0
1
Order By: Relevance
“…Zhang and co-authors recently reported an excellent chemoselectivity of an intramolecular allylic CeH amination versus a C]C aziridination using a D 2h -symmetric cobalt porphyrin catalyst [22]. A similar trend was also observed by us [26] for the amination of cyclohexene catalysed by Co(TPP) (TPP ¼ dianion of tetraphenyl porphyrin).…”
Section: Introductionsupporting
confidence: 55%
“…Zhang and co-authors recently reported an excellent chemoselectivity of an intramolecular allylic CeH amination versus a C]C aziridination using a D 2h -symmetric cobalt porphyrin catalyst [22]. A similar trend was also observed by us [26] for the amination of cyclohexene catalysed by Co(TPP) (TPP ¼ dianion of tetraphenyl porphyrin).…”
Section: Introductionsupporting
confidence: 55%
“…6 These Co(II)-based metalloradical catalysts have proven to be unusually effective on the activation of various organic azides, including sulfonyl, 7 phosphoryl, 8 carbonyl 9 and aryl 10 azides, for amination of broad classes of C–H bonds under neutral and non-oxidative conditions. 11 Particularly, Co(II) complexes of D 2h -symmetric amidoporphyrins [Co( D 2h -Por)] have revealed uncommon catalytic capacity for efficient intramolecular amination of strong primary C–H bonds 7b,8 and have also displayed excellent chemoselectivity for intramolecular allylic C–H amination over the competitive C=C aziridination. 7c Several lines of experimental and computational evidence back the radical mechanism of Co(II)/azide-based C–H amination that involves an unusual Co(III)-nitrene radical intermediate undergoing a stepwise radical abstraction-substitution pathway.…”
mentioning
confidence: 99%
“…11 Particularly, Co(II) complexes of D 2h -symmetric amidoporphyrins [Co( D 2h -Por)] have revealed uncommon catalytic capacity for efficient intramolecular amination of strong primary C–H bonds 7b,8 and have also displayed excellent chemoselectivity for intramolecular allylic C–H amination over the competitive C=C aziridination. 7c Several lines of experimental and computational evidence back the radical mechanism of Co(II)/azide-based C–H amination that involves an unusual Co(III)-nitrene radical intermediate undergoing a stepwise radical abstraction-substitution pathway. 7b,7c,12,13 Considering the non-electrophilic nature of this radical mechanism, which is fundamentally different from the electrophilic metallonitrene mechanism shared by the widely-studied Rh 2 - and other closed-shell systems, we envisaged the possibility of addressing the aforementioned challenge of intramolecular electron-deficient C–H amination through Co(II)-based metalloradical catalysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations